An Absolute Electric Current Probe Based on the Faraday Effect - Caton, W. (J Res Natl Bur Stand (1977), 1984)
This paper describes the design, construction, and testing of a probe for the measurement of electric current in a circuit. This measurement is performed by using Faraday rotation produced in a beam of polarized light that encircles the current-carrying conductor. Such a probe is an absolute instrument whose calibration only depends upon the Verdet constant of the rotative medium and is independent of the dimensions or positions of the light path relative to the current. The time resolution of the probe is the optical transit time about the closed path and can in practice be reduced to a few nanoseconds.